Interpreting Music - Kramer, Lawrence, 1946- (Book collections on Project MUSE., 2011)
This is a comprehensive essay on musical meaning and performing music meaningfully - 'interpreting music' in both senses of the term. The author argues that music, far from being closed to interpretation is the paradigm of interpretation in general.